Treatment of postoperative intestinal dysfunction of hirschsprung's disease based on the principle of “anorectal balance” - Tian, Li; Ma, Chensen; Deng, Zhengdong; Zhu, Tianqi; Zhao, Xiang; He, Ying; Wei, Mingfa; Feng, Jiexiong; Yu, Donghai (Frontiers in Surgery, 2022)
Purpose: Radical surgery is the most effective treatment for Hirschsprung's disease. However, some children still have symptoms of intestinal dysfunction such as constipation, abdominal distension, and recurrent enterocolitis after operation. The purpose of this study was to evaluate treatment outcomes of postoperative intestinal dysfunction in children with Hirschsprung's disease by using the principle of "anorectal balance". Methods: The clinical data of postoperative intestinal dysfunction in children with Hirschsprung's disease in the single treatment group from July 2019 to July 2021 were retrospectively analyzed. All the enrolled children underwent botulinum toxin injection (2.5 U/kg); 3 to 6 months later, the injection was performed again; the children who had received more than two botulinum toxin injections underwent the internal sphincter myectomy. Anorectal manometry was performed routinely after operation, and abdominal distension and defecation were recorded. Results: A total of thirty children with postoperative intestinal dysfunction underwent radical surgery for Hirschsprung's disease were included in this study. Symptoms of constipation, abdominal distension and enterocolitis were improved after botulinum toxin injections in most children compared to before surgery (P<0.01). After re-injection of botulinum toxin in twelve children, the frequency of defecation increased, the anal resting pressure decreased, and the clinical symptoms were relieved again (P<0.05). Eleven children underwent internal sphincter myectomy, and the symptoms of constipation, abdominal distension and enterocolitis were significantly improved after the operation（P<0.01）. Conclusion: Botulinum toxin injection and internal sphincter myectomy based on the principle of "anorectal balance" can effectively reduce the resting pressure of the anus and relieve intestinal dysfunction, and have satisfactory clinical effect.